2012
DOI: 10.1002/adsc.201200608
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of Tertiary Anilines with Maleimides under Visible Light Redox Catalysis

Abstract: Tertiary anilines can be prompted to react with N‐aryl‐ and N‐benzylmaleimides to form tetrahydroquinoline products under photocatalysis using visible light irradiation, the ruthenium or iridium complexes Ru(bpy)3Cl2 or Ir(ppy)2(dtbbpy)PF6 as catalyst, and air as terminal oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 61 publications
2
94
0
1
Order By: Relevance
“…[47] In 2012, Zhou and co-workers reported visible-light-mediated [4+2] benzannulation reactions between biaryldiazonium salts 151 (Scheme 28) and alkynes 152, producing 9-substituted or 9,10-disubstituted phenanthrenes 153 in moderate to high yields. [47] In 2012, Zhou and co-workers reported visible-light-mediated [4+2] benzannulation reactions between biaryldiazonium salts 151 (Scheme 28) and alkynes 152, producing 9-substituted or 9,10-disubstituted phenanthrenes 153 in moderate to high yields.…”
Section: The Formation Of Six-membered Ring Systemsmentioning
confidence: 99%
“…[47] In 2012, Zhou and co-workers reported visible-light-mediated [4+2] benzannulation reactions between biaryldiazonium salts 151 (Scheme 28) and alkynes 152, producing 9-substituted or 9,10-disubstituted phenanthrenes 153 in moderate to high yields. [47] In 2012, Zhou and co-workers reported visible-light-mediated [4+2] benzannulation reactions between biaryldiazonium salts 151 (Scheme 28) and alkynes 152, producing 9-substituted or 9,10-disubstituted phenanthrenes 153 in moderate to high yields.…”
Section: The Formation Of Six-membered Ring Systemsmentioning
confidence: 99%
“…[2a, 17] LiPF 6 as aL ewis acid cocatalyst plays asignificant role,that is,accelerating the nucleophilic addition of the radical A to 2,and stablizing the formed radical B.T he radical B cannot oxidize the radical anion DPZ HC À and the subsequent cyclization step becomes possible. To explore the mechanism, we firstly attempted to oxidize 1a to the iminium D as the Mannich acceptor,byemploying BrCCl 3 [17] in DMF at 25 8 8Cand under visible-light irradiation, but the desired 5a was not detected after 4.0 equivalents of 2a and Et 3 Nw ere added and the reaction run for 24 h( Scheme 2b). [13d-e] However,t he results in Table 3( Conditions B) indicated that only vinylogous Mannich-type products (5) were obtained.…”
mentioning
confidence: 99%
“…This per‐oxy radical may compete in the generation of α‐aminoalkyl radicals and thereby participate in the follow‐up cyclisation process. To examine this possibility, we replicated the experiment reported by Yu and Bian using H 2 TPP, which is a common photosensitizer (Scheme b) . The reaction proceeded slowly with much inferior yield of the product, thus excluding the role of NiTPP only as photosensitizer instead of a photoredox catalyst.…”
Section: Resultsmentioning
confidence: 96%